Religieuse Kommunikasie - Willem de Klerk (Communicare)
THIS article explores the possibilities of religious communication as a field of study In the science of communication. The author adopts the point of view that religious communication is experienced by a large number of people. They claim the existence of a sender, messages, media, receivers, feed back, Interaction and communicative relations. "Explanations" for this religious phenomenon are presented by the sciences of theology, philosophy, psychology and sociology. The communication science should take cognisance of these findings. The focus of the communication sciences should fall on the religious response or expression or feedback by Individuals and groups. Religious language is one field of study. Another field of study is the communication dynamics as experienced in religious cults, symbols, ceremonies and acts. The first priority should be to identify and define the specific field of the communication sciences within the religious phenomena. Then, themes for research can be explored. In this article attention is given to different psychological "explanations" for religious communication e.g. the theory of projection, Infantilism, numinous experiences, archetypes, the pursuit of value systems, etc. Exploratory formulations for the religious communication of these theories are presented in this article. The transcendental explanation, namely the pre-scientific premise that God exists, is also discussed. Here, the accent for the communication science falls on responses which are divided into religious sensitivity, directional and expression responses.